ANALISIS RESPON PASAR TERHADAP PENGUMUMAN SAHAM BONUS PADA BURSA EFEK INDONESIA - Siti Murtopingah; Rina Mudjiyanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
This study is to analysis the market response to the announcement of bonus share in Indonesia Stock Exchange. The response is indicated by the abnormal return. The method applied is event study using windows 15 days, 7 days before announcement and 7 days after announcement. The sample was selected purposively method in observation period of 2008 – 2014. Along the period, 24 companies were taken as sample. A hypothesis testing was done using paired sample t test. The statistical analysis proves that there is no significant difference of abnormal return between the period before and the period after the bonus share announcement.Keywords : Bonus Share, Market Response, Abnormal Return, Event Study